Study of Metal Corrosion Resistance Using Chemical Inhibitors in Concrete - Dlhin, Faeza Saleh (Journal of Progress in Civil Engineering, 2025)
Hydrozincite, Zn5 (CO3)2 (OH) 6, was recently found to play a key role in reducing corrosion product flaking on Cu-Zn alloys. A fundamental study was undertaken to explore the underlying mechanisms, in particular why hydrozincite can suppress the interaction between chloride and the alloy surface. Hydrozincite could be formed by exposure of Cu40Zn to air at 70% relative humidity and 1000 ppm of CO2 resulting in a surface of decreased wettability. It presents reduces the initial spreading ability of NaCl-containing droplets and lower the overall initial corrosion rate when the alloy is exposed to pre-deposited NaCl and wet / dry cycles.